Spectroscopic Analysis Study of Laser-Created Zinc Plasma (Baghdad Science Journal, 2024)
Through optical emission spectroscopy, zinc (Zn) plasma produced on the basis of a laser can be investigated in the proposed study. Zinc plasma spectral emissions were studied as a function of laser energy (200, 300, 400, and 500) mJ. Record plasma emission with a 100 ns integration time. The spectral lines of zinc were determined, and the electron temperature ( ) and electron density ( ) were studied using Boltzmann diagrams. It is noted from the results that as the laser energies increase, the values of and rise as well, as the values range from eV for electron temperature, while the electron density values range . Also, in this paper, other parameters investigated included Debye length (_D), FWHM, and plasma frequency (fp).